Enhancing the hydrogen storage capacity of Pd-functionalized multi-walled carbon nanotubes - Singh, Priyanka; Kulkarni, Mukta V.; Gokhale, Suresh P.; Chikkali, Samir H.; Kulkarni, Chandrashekhar V. (Applied Surface Science, 2012)
We demonstrate that the hydrogen storage capacity of multi-walled carbon nanotubes can be enhanced by polyvinylpyrrolidone functionalization. The polyvinylpyrrolidone acts as a stabilizing agent for Pd-nanoparticles, reduces their size and facilitates their uniform and enhanced loading onto multi-walled carbon nanotubes. According to sorption studies, the polyvinylpyrrolidone capping and consequent nanostructural modification enables 2.3 times more hydrogen adsorption than mere Pd-functionalization of multi-walled carbon nanotubes. Corresponding morphological changes before and after polyvinylpyrrolidone capping, characterized using Raman Spectroscopy, X-ray diffraction, TEM and thermal analysis techniques, are also presented. The results contribute towards increasing the efficiency of hydrogen based sustainable energy sources. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Hydrogen based energy sources; Hydrogen storage capacity; Multiwalled carbon nanotubes; Pd functionalization; PVP capping